Nome beach with tents, supplies, and carts, Nome, Alaska, between 1898 and 1901 - Hester, Wilhelm, 1872-1947 (1898)
PH Coll 318.1015 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number